Viral justice? Online justice-seeking, intimate partner violence and affective contagion - Wood, Mark (Theoretical criminology, 2019)
What has been termed the survivor selfie is a recent and growing phenomenon whereby survivors of intimate partner violence or their close supporters upload graphic photos and accounts of their injuries and suffering to social media. In this article, we examine how the like economy of Facebook can lead to the rapid circulation of survivor selfies to large audiences, and in doing so, generate what we term viral justice: the outcome of a victim's online justice-seeking post ‘going viral' and quickly being viewed and shared-on by thousands of social media users. Through examining the trajectory and impact of one particular case—Ashlee Savins's viral survivor selfie—we identify the technological preconditions of viral justice and three of its key dimensions: affective contagion; swarm sociality; and movement power. Through discussing the speed, sociality and contagion of viral justice, we critically consider some of its implications for online justice-seeking, and responding to intimate partner violence.